Assessment of Water Quality in Kemajuan Lake: A Comparative Study with National Lake Water Quality Criteria and Standards (NLWQS) - Muhammad Hafiq Afifi Azman; Rafidah Hamdan; Zarina Md Ali; Zuhaib Siddiqui (International Journal of Sustainable Construction Engineering and Technology, 2025)
Water is vital for life and supports the agriculture, industry, and recreation sectors. Lentic systems, including lakes, are integral to global hydrological cycles but are sensitive to changes in land use and human activities. The National Lake Water Quality Criteria and Standards (NLWQS) provide a framework for assessing and managing lake water quality to address pollution and maintain Malaysia’s ecological balance. This study evaluated the water quality of Kemajuan Lake, UTHM, a Category A lake used for recreation and flood mitigation, based on the NLWQS. The water quality assessment of Kemajuan Lake was carried out weekly over a 10-month period (40 weeks). In-situ measurements recorded the pH, dissolved oxygen (DO), DO saturation, and temperature, while water transparency was assessed using a Secchi disc. Laboratory analysis included biochemical oxygen demand (BOD₅), chemical oxygen demand (COD), total suspended solids (TSS), ammoniacal nitrogen (AN), nitrate (NO₃⁻), total phosphorus (TP), chlorophyll-a (Chl-a), and heavy metals (As, Cd, Pb, Ni, and Hg). Analysis based on the NLWQS (Category A) revealed that parameters such as pH (6.80±0.83), temperature (27.94±2.03ºC), turbidity (20.70±3.19 NTU), TSS (15.45±4.43 mg/L), water transparency (1.28±0.12 m), nitrate (0.36±0.15 mg/L), and selected heavy metals which were As (0.003±0.001 mg/L), Cd (0.00003±0.00001 mg/L), Pb (0.0005±0.0004 mg/L), Ni (0.0001±0.000 mg/L), and Hg (0.0001±0.0001 mg/L) complied with safety standards for body contact. However, DO (4.12±0.54 mg/L), DO % saturation (57.23±5.51%), COD (19.88±5.72 mg/L), BOD₅ (9.43±2.67 mg/L), Chl-a (26.30±12.31 µg/L), TP (0.55±0.36 mg/L), and AN (0.55±0.15 mg/L) exceeded permissible limit, rendering Kemajuan Lake unsuitable for recreational activities due to non-compliance with water quality parameters.